Principal-Based Leadership Based on Micro-Habits Coaching in Improving The Pedagogic Performance of Teachers at Smpn 1 Maniis - Suharyanto Soro; Nana Herdiana Abdul Rahman; Sair Apipudin; Asep Muhamad Ilyas (Civiliza Publishing, Indonesia., 2026)
The professional development needs of teachers still rely on formal training programs. Principal's leadership interventions are only sustainable and do not focus on consistent behavior change. Micro-habits coaching is seen as an approach that is able to foster positive habits through systematic mentoring, regular reflection, and directed feedback so that it has the potential to significantly strengthen teachers' pedagogic competence. This study aims to describe the effectiveness of principal leadership based on micro-habits coaching in improving teachers' pedagogic performance. This research uses a qualitative research paradigm with a case study approach. Data were collected through non-participatory observations, in-depth interviews, and documentation. Respondents were selected by purposive sampling. The findings of the study show that (1) the leadership of the principal has implemented micro-habits coaching can build a culture of continuous learning in the school environment; (2) The principal plays the role of a coach who facilitates teachers to identify areas of self-development, set realistic micro-targets, monitor progress, and provide positive reinforcement for the achievements obtained. This study concludes that micro-habits coaching based leadership is an effective strategy to improve teachers' pedagogic performance and is implemented more widely as a model of sustainable professional development in schools.